Strategies and Policies of East Java Regional Government in Encouraging The Spread of Investment and Building The Investment Climate 2021-2025 - Sutarmin; Saibat (Economic and Bussiness Faculty, Dr Soetomo University, 2022)
Abstract. This research was conducted at the Investment and One-Stop Services Office / Dinas PenanamanModal dan Pelayanan Terpadu Satu Pintu (DPMPTSP) of East Java Province. This research aims to provideinformation related to Promoting Strategy and Policy, expanding the Spread of Investment and building theInvestment Climate in East Java. This study uses a qualitative method with a descriptive approach. Datacollection techniques can be done by observation, questionnaire, documentation and a combination of all. Thedata sources used in this study are primary data and secondary data. The informants in the study were theOffice in the East Java Provincial Government, Regency / City DPMPTSP in East Java, Internal Affairs in theEast Java Province DPMPTSP. While the sampling used in this study is saturated sampling. Based on the resultsof the study it was concluded that 1. Improved coordination between the Central Government, ProvincialGovernment and Regency / City Governments of East Java, 2. designing an online-based market place that sellsInvestment Project Ready to Offer (IPRO) projects 3. Improving the investment climate to make it moreconducive and overlapping regulations, increasing bureaucratic efficiency through simplifying businesslicensing procedures, regulations and Law Enforcement. 4. Encouraging the creation of a one-door IntegratedLicensing Service institution in the Regency/City. 5. Encouraging investment in businesses that are lessattractive to investors. 6. Encouraging investment in areas that have so far had minimal investment, such as thecentral and southern regions of East Java. 7. Encouraging the opening of new industrial areas, especially outsidethe Surabaya, Gresik, Sidoarjo and Mojokerto areas. Improving the investment climate so that it is moreconducive and regulations are overlapping, increasing bureaucratic efficiency through simplifying businesslicensing procedures, regulations and Law Enforcement. 4. Encouraging the creation of a one-door IntegratedLicensing Service institution in the Regency/City. 5. Encouraging investment in businesses that are lessattractive to investors. 6. Encouraging investment in areas that have so far had minimal investment, such as thecentral and southern regions of East Java. 7. Encouraging the opening of new industrial areas, especially outsidethe Surabaya, Gresik, Sidoarjo and Mojokerto areas. Improving the investment climate so that it is moreconducive and regulations are overlapping, increasing bureaucratic efficiency through simplifying businesslicensing procedures, regulations and Law Enforcement. 4. Encouraging the creation of a one-door IntegratedLicensing Service institution in the Regency/City. 5. Encouraging investment in businesses that are lessattractive to investors. 6. Encouraging investment in areas that have so far had minimal investment, such as thecentral and southern regions of East Java. 7. Encouraging the opening of new industrial areas, especially outsidethe Surabaya, Gresik, Sidoarjo and Mojokerto areas. Encouraging the creation of a one-door IntegratedLicensing Service institution in the Regency/City. 5. Encouraging investment in businesses that are lessattractive to investors. 6. Encouraging investment in areas that have so far had minimal investment, such as thecentral and southern regions of East Java. 7. Encouraging the opening of new industrial areas, especially outsidethe Surabaya, Gresik, Sidoarjo and Mojokerto areas. Encouraging the creation of a one-door IntegratedLicensing Service institution in the Regency/City. 5. Encouraging investment in businesses that are lessattractive to investors. 6. Encouraging investment in areas that have so far had minimal investment, such as thecentral and southern regions of East Java. 7. Encouraging the opening of new industrial areas, especially outsidethe Surabaya, Gresik, Sidoarjo and Mojokerto areas. Keywords: Investment; Equity; Development